Working Life of the I-beam with a Crack. (2015) - Djoković, Jelena M.; Nikolić, Ružica R.; Bujnak, Jan
Abstract: The I-beam containing a crack, loaded by the bending moment and the axial force is considered in this paper. The Mode I stress intensity factor for the beam is determined based on classical expressions with taking into account the cross-section warping by the reduced force and moment, which are valid for the thin-walled beams. On diagrams representing the Mode I stress intensity factor variation with normalized crack length, in intersections of curves for various values of loads and fracture toughness of the beam material, one obtains values of the crack length for which the fracture of the particular beam would occur. The adopted beam material is steel Č.0562 (St 52-3). The Paris law was used for determination of the average crack growth speed. From the diagram of the ΔK (difference between the stress intensity maximum minus and minimum values) variation in terms of the crack length, one can notice that at the beginning, it increases linearly with the crack length, and then, after a certain value of the crack length was reached, it increases abruptly. This could be explained by the fact that the crack length begins to increase suddenly after certain number of load cycles was reached.